Peningkatan Hasil Belajar dengan Model Pembelajaran Berbasis Masalah Siswa Kelas X TITL SMK Cokroaminoto Kotamobagu - Rorimpandey, Rian; Detu, Hamid; Rapar, Jocke; Memah, Viverdy (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2022)
Abstract– This study aims to apply and analyze a problem-based learning model in a group of students of Class X Electrical Power Installation Engineering (in Indonesian abbreviated TITL) SMK Cokroaminoto Kotamobagu in Basic Electronics learning. This research hypothesizes that if you apply a problem-based learning model, it can improve student learning outcomes. Based on the research in the first cycle of 22 students, only 8 students (26%) achieved learning mastery with a value of 75. While in the second cycle, it increased to 22 (all) students (100%) who achieved learning mastery. Based on the results of this study, it can be seen that using a problem-based learning model can improve learning outcomes in Basic Electronics for class X TITL students at SMK Cokroaminoto Kotamobagu. Abstrak– Penelitian ini bertujuan untuk menerapkan dan menganalisis model pembelajaran berbasis masalah pada kelompok siswa Kelas X Teknik Instalasi Tenaga Listrik (TITL) SMK Cokroaminoto Kotamobagu pada pembelajaran Elektronika Dasar. Hipotesis penelitian ini adalah apabila menerapkan model pembelajaran berbasis masalah maka dapat meningkatkan hasil belajar siswa. Berdasarkan penelitian pada siklus I dari 22 siswa hanya 8 orang siswa (26%) yang mencapai ketuntasan belajar dengan nilai ≤ 75. Sedangkan pada siklus II mengalami peningkatan menjadi 22 (semua) siswa (100%) yang mencapai ketuntasan belajar. Berdasarkan hasil penelitian ini maka dapat dilihat bahwa dengan menggunakan model pembelajaran berbasis masalah dapat meningkatkan hasil belajar Elektronika Dasar siswa kelas X TITL SMK Cokroaminoto Kotamobagu.